FACTORS INFLUENCING THE ADOPTION OF CLOUD COMPUTING AMONG MSMES IN BANDUNG CITY USING EXTENDED UTAUT2 WITH TECHNOLOGY READINESS - Valencia Jennice (Ikatan Dosen Menulis, 2024)
With the evolution of the world, digital technology has transformed information, communication, and connectivity, largely driven by Industry 4.0 technologies, among which cloud computing stands out. Cloud computing facilitates data storage and information exchange via the internet, offering significant advantages to businesses, particularly Micro, Small, and Medium Enterprises (MSMEs), by enabling them to manage data independently and efficiently. The adoption of cloud computing is anticipated to advance digitalization in Indonesia, potentially increasing income and creating employment opportunities in the coming years. This research aims to identify the factors influencing cloud computing adoption among MSMEs in Bandung City. Utilizing the Extended Unified Theory of Acceptance and Use of Technology (UTAUT2) with Technology Readiness, the study collected 158 valid responses through an online questionnaire from MSMEs that have utilized or are currently utilizing cloud computing services in Bandung City. The data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The findings reveal that Performance Expectancy, Effort Expectancy, Facilitating Conditions, Habit, and Optimism positively influence the intention of MSMEs to adopt cloud computing. Furthermore, Behavioral Intention positively affects Actual Usage. This research shows that MSMEs with a strong intention to adopt cloud computing are more likely to integrate it into their daily operations. Enhancing MSMEs' knowledge and digital skills can further facilitate their use of cloud computing services, given their positive perception of these services. Recommendations for MSMEs include focusing on improving digital skills, while the government should implement digital literacy programs to support MSMEs in using cloud computing. However, this study is limited to MSMEs in Bandung City, which may restrict the generalizability of the findings. Future research should explore the types of services used by MSMEs, incorporate additional variables, employ different methodological approaches, and consider a broader sample.